Activities and genetic interactions of fission yeast Aps1, a Nudix-type inositol pyrophosphatase and inorganic polyphosphatase - Shreya Ghosh; Ana M. Sanchez; Beate Schwer; Isabel Prucker; Nikolaus Jork; Henning J. Jessen; Stewart Shuman (mBio, 2024)
ABSTRACT Inositol pyrophosphate 1,5-IP8 regulates expression of a fission yeast phosphate homeostasis regulon, comprising phosphate acquisition genes pho1, pho84, and tgp1, via its action as an agonist of precocious termination of transcription of the upstream lncRNAs that repress PHO mRNA synthesis. 1,5-IP8 levels are dictated by a balance between the Asp1 N-terminal kinase domain that converts 5-IP7 to 1,5-IP8 and three inositol pyrophosphatases—the Asp1 C-terminal domain (a histidine acid phosphatase), Siw14 (a cysteinyl-phosphatase), and Aps1 (a Nudix enzyme). In this study, we report the biochemical and genetic characterization of Aps1 and an analysis of the effects of Asp1, Siw14, and Aps1 mutations on cellular inositol pyrophosphate levels. We find that Aps1’s substrate repertoire embraces inorganic polyphosphates, 5-IP7, 1-IP7, and 1,5-IP8. Aps1 displays a ~twofold preference for hydrolysis of 1-IP7 versus 5-IP7 and aps1∆ cells have twofold higher levels of 1-IP7 vis-à-vis wild-type cells. While neither Aps1 nor Siw14 is essential for growth, an aps1∆ siw14∆ double mutation is lethal on YES medium. This lethality is a manifestation of IP8 toxicosis, whereby excessive 1,5-IP8 drives derepression of tgp1, leading to Tgp1-mediated uptake of glycerophosphocholine. We were able to recover an aps1∆ siw14∆ mutant on ePMGT medium lacking glycerophosphocholine and to suppress the severe growth defect of aps1∆ siw14∆ on YES by deleting tgp1. However, the severe growth defect of an aps1∆ asp1-H397A strain could not be alleviated by deleting tgp1, suggesting that 1,5-IP8 levels in this double-pyrophosphatase mutant exceed a threshold beyond which overzealous termination affects other genes, which results in cytotoxicity.IMPORTANCERepression of the fission yeast PHO genes tgp1, pho1, and pho84 by lncRNA-mediated interference is sensitive to changes in the metabolism of 1,5-IP8, a signaling molecule that acts as an agonist of precocious lncRNA termination. 1,5-IP8 is formed by phosphorylation of 5-IP7 and catabolized by inositol pyrophosphatases from three distinct enzyme families: Asp1 (a histidine acid phosphatase), Siw14 (a cysteinyl phosphatase), and Aps1 (a Nudix hydrolase). This study entails a biochemical characterization of Aps1 and an analysis of how Asp1, Siw14, and Aps1 mutations impact growth and inositol pyrophosphate pools in vivo. Aps1 catalyzes hydrolysis of inorganic polyphosphates, 5-IP7, 1-IP7, and 1,5-IP8 in vitro, with a ~twofold preference for 1-IP7 over 5-IP7. aps1∆ cells have twofold higher levels of 1-IP7 than wild-type cells. An aps1∆ siw14∆ double mutation is lethal because excessive 1,5-IP8 triggers derepression of tgp1, leading to toxic uptake of glycerophosphocholine.